WEBSITE DESIGN INFORMATION SYSTEM OF RECORDING OFFENS AND PUNISHMENT STUDENTS SMK MUHAMMADIYAH 8 SILIRAGUNG USE WATERFALL DEVELOPMENT METHOD - Putri Julisa Martadina; Sulaibatul Aslamiyah (Fakultas Teknik Universitas Lambung Mangkurat, 2024)
Educational institutions as learning centers are prepared so they keep up through developments, especially regarding the use of information systems which are expected to facilitate the completion of work effectively and in an efficient time so institutions can improve their quality achievements. In this case, SMK Muhammadiyah 8 Siliragung experienced issues in the counselling division regarding recording violations and sanctions which required plenty of time to process and search for the required documents manually. To overcome issues, an information system for recording, as well as storing the history of violations carried out in a computerized manner efficiently to search for history data. This system development uses waterfall development methodology with a MySQL storage database and WEB-based PHP programming language. This research succeeded in identifying the needs through data collection methods, analysis of needs planning and observation meanwhile the system is equipped with a login and logout, a student data, a record, an administration letter, as well as a problematic student data report feature with a violation filter. This information system have been to overcome the issues.